The Effect of Telecommunication Infrastructure Development on Economic Growth in ASEAN - prasetyo, galih adi (Jurnal Ilmu Ekonomi Terapan, 2019)
This study aims to determine the effect of the development of telecommunications infrastructure to economic growth in ASEAN. Generalized Method of Moment (GMM) is used to test how telecommunication infrastructure development to economic growth in ASEAN. This study uses a dynamic panel data from 10 ASEAN countries in the period 2000-2013. Variables used in this research is the GDP growth, the development of telecommunicationinfrastructure index, foreign direct investment, trade openness, and urbanization rate. Tests were performed using STATA 13.0 software shows the use sys-GMM better than diff- GMM.The results of this study indicate the development of telecommunications infrastructure significantly affect economic growth but had negative relationships. Based on the theory of demand following hypothesis (DFH) economic growth leads to the development of telecommunications infrastructure. The impact of telecommunications infrastructure development is only emerge through the product or outcome of economic growth. Telecommunications infrastructure development is considered as the impact of economic growth continues to increase. Keywords: Telecommunication, Infrastructure, Dynamic Panel, Sys-GMM JEL: C01; H54